Carbonate chemistry in the Mertz Polynya (East Antarctica): Biological and physical modification of dense water outflows and the export of anthropogenic CO2. Issue 1 (7th January 2014) - Shadwick, E. H.; Tilbrook, B.; Williams, G. D.
<x xml:space="preserve">Abstract</x> [1] Dense shelf water (DSW) is formed in East Antarctica from enhanced sea‐ice production driven by air‐sea interaction in coastal polynyas. Cross‐shelf export and downslope mixing of this DSW produces Antarctic Bottom Water, contributing to the lower limb of the global overturning circulation. We present biogeochemical observations from the Mertz Polynya region in summer 2007/2008, with additional observations from spring 2001 and winter 1996. The seasonal changes in mixed‐layer carbonate chemistry are driven by a combination of air‐sea CO2 exchange, biological activity and the formation and melt of sea‐ice. The air‐sea fluxes in 2008 were ∼15 mmol C m−2 d−1, and net community production, estimated from the summertime surface dissolved inorganic carbon (DIC) deficit, ranged from 0.9 to 1.2 mol C m−2 yr−1. We show that biological modification of carbonate chemistry over the shelf in summer preconditions the DSW outflows from the Adélie Depression. This process appears to supply both organic material, and water depleted in CO2, and with enhanced carbonate saturation state (relative to inflowing water), to coral communities on the slope. We combined model‐based transports of exported DSW with the natural and anthropogenic (Cant) carbon concentrations and estimate that the annual outflows of DIC and Cant from the Mertz Polynya range from 320 to 560 Tg C yr−1, and from 3 to 6 Tg Cant yr−1, respectively. The formation and export of dense water from this region, and by extension all similar polynyas around Antarctica, is an effective mechanism for the transfer of anthropogenic carbon into the deep ocean.